101 job interview questions you'll never fear again - Reed, James (New York A Plume Book, 2014)
Learn the secrets to excelling at job interviews, directly from top interviewers and recruiters. You can't prepare an answer for every interview question. So, of the thousands of questions a potential employer might ask, which ones will they ask? And what should you say? After extensive research among hundreds of interviewers and thousands of interviewees, finally here's the book that will give you the answer."
"Originally published in Great Britain as Why you? by Portfolio, an imprint of Penguin Random House UK"--Verso of title page.
Keywords: Employment interviewing